Enabling the Metaverse. Whitepaper on international user preferences, business models and innovation processes in the Metaverse - Daniel Duwe; Malte Busch; Marion A. Weissenberger-Eibl (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2022)
The Metaverse is on everyone's lips. After all, it is being treated as the successor to the Internet. Companies around the world are investing millions in its development. But so far it is unclear whether the preferences of people from different parts of the world about the Metaverse coincide or diverge. Therefore, over 1,500 people from Germany, the US and China were surveyed about their preferences in using the Metaverse. The results are presented in this whitepaper. In addition, an introductory overview of relevant functions and technologies is given and, following the survey results, it is shown what impact the Metaverse can have on companies' business models and innovation processes and how they can approach the Metaverse.
Keywords: 650; Metaverse; Metaversum; Preferences; Business Models; Innovation Process